Fiber Optic Shape Sensors: A comprehensive review - Floris, Ignazio; Adam, Jose M.; Calderón, Pedro A.; Sales, Salvador (Optics and lasers in engineering, 2021)
•Optical Fiber Sensing offers a valid alternative to existing shape sensing methods.•This technology can bring remarkable improvements to different fields.•This paper presents a review of the state of the art of Fiber Optic Shape Sensors.•The paper aspires to be an exhaustive guide for anyone interested in the field. Fiber Optic Shape Sensing is an innovative Optical Fiber Sensing Technology that uses a fiber optic cable to continuously track the 3D shape and position of a dynamic object (with unknown motion) in real-time without visual contact. This technology offers a valid alternative to existing shape sensing methods, thanks to a combination of advantages (including ease of installation, intrinsic safety, compactness, flexibility, electrically passive operation, resistance to harsh environments and corrosion, no need for proximity or computational or numerical models to reconstruct shape) that can bring remarkable improvements to the fields of Civil, Mechanical and Aerospace Engineering, Biomedicine and Medicine. A considerable research effort has been dedicated to this subject in the last twenty years. This paper presents an ambitious review of the current state of the art of Fiber Optic Shape Sensors (FOSS) based on Optical Multicore Fibers (MCF) or multiple optical single-core fibers with embedded strain sensors and provides a comprehensive analysis of a wide range of aspects, comprising: (1) existing alternative technologies; (2) an overview of optical fiber sensors (3) characteristics and advantages of fiber optic shape sensors; (4) historical achievements; (5) applications; (6) performance and error analysis; and (7) present and future perspectives.